2019
DOI: 10.1177/1461348419874973
|View full text |Cite
|
Sign up to set email alerts
|

Release oscillation in a hollow fiber – Part 2: The effect of its frequency on ions release and experimental verification

Abstract: The capillary oscillation in a hollow fiber greatly affects the process of ions release. Its approximate frequency is obtained, revealing a lower frequency predicts a longer release process, and the main factor affecting the frequency is studied theoretically and verified experimentally. The oscillation release can be also extended to drug release in tissue engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Interestingly, the antimicrobial activity of AgNPs showed long-lasting protection against bacteria compared with povidone iodine. The remaining inhibition zone of the AgNP gel after 48 h could be caused by the action of Ag ions released from AgNPs [ 55 , 56 ]. Ag ions can be released in increments, depending on the oxidation of AgNPs by oxygen, antibacterial substances, chloride and peroxide.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the antimicrobial activity of AgNPs showed long-lasting protection against bacteria compared with povidone iodine. The remaining inhibition zone of the AgNP gel after 48 h could be caused by the action of Ag ions released from AgNPs [ 55 , 56 ]. Ag ions can be released in increments, depending on the oxidation of AgNPs by oxygen, antibacterial substances, chloride and peroxide.…”
Section: Discussionmentioning
confidence: 99%
“…In 1.0 ml of phosphate-buffered saline (PBS) at room temperature, samples of SNM (30 mg) thermo crosslinked with 5% PVA were first swollen for 5 min by shaking (at 100 rpm) ( Lin et al, 2019 ). As soon as the sample reached equilibrium, it was placed in the center of a copper coil.…”
Section: Methodsmentioning
confidence: 99%
“…Cell orientation can also be guided by the boundary-induced force induced by adjacent nanofibers. Besides, Lin et al [19,20,49] studied the release oscillation in a hollow fiber and established a fractional model. The results showed that the ions release depends upon the low frequency property.…”
Section: Thermal Oscillation and Its Low Frequency Propertymentioning
confidence: 99%